The World of Books and Libraries in the 18th Century. Bibliotheca Metropolitana in Zagreb - Botica, Dubravka (2011)
Bibliotheca Metropolitana, or Metropolitan Library, the Zagreb Arch-Diocesan Library, is one of the largest and most significant collections of books and manuscripts in both Croatia and in the south-eastern part of Central Europe. The origins of the library go back to 1094, the foundation year of the Zagreb Diocese. In 1394, the first handwritten catalogue of 113 books was created. In 1640, the Zagreb Chapter introduced important regulations on the work of the library, and the first code of practice entitled “Library Regulations” was drawn up at the end of the 17th century. An important role in the history of the Metropolitan Library was played by two bishops, Ignacije Aleksandar Mikulić and Maksimilijan Vrhovac. In several years' time, Bishop Mikulić (1688-1694) built a library and established a fund. He made the library stock significantly richer in 1690 by buying a collection of polyhistor from Kranj, Janez Vaikard Valvasor (Johann Weikhard Freiherr von Valvasor). Bishop Maksimilian Vrhovac (1787-1827) was also one of the main protagonists of the expansion of the library stock. He acquired books of various contents from all over Europe. In 1846, during the office of Archbishop Haulik, the library was open to the public. After the earthquake in 1880, the fortification tower housing the Metropolitan Library was destroyed. In 1914, according to the contract signed by the Zagreb Archdiocese, the Metropolitan Chapter and the University Library, the new home of the Metropolitan Library was the new building of the University Library, designed in 1913 by Rudolf Lubinsky. After the National and University Library moved to a newly constructed building in 1995, the Metropolitan Library has shared the space of the older building with the Croatian State Archives. The Metropolitan Library has in its holdings about 60 000 items which form the collections of old manuscripts, incunabula and printed books, atlases and maps. The library stock provides a source for various studies in the fields of history, historiography, art history, philology, music history, history of printing and publishing. A large number of items are related to natural sciences as well. However, incomplete and disparate cataloguing and inappropriate conditions limits the use of this collection. At the beginning of the 20th century, Ljubo Ivančan created a hand-written library catalogue containing 36 boxes of cards. Alphabetical catalogue of titles and authors in Valvasor's collection, entitled Bibliotheca Valvasoriana. Catalogue of Janez Vajkard Valvasor's Library, was published in 1995 on the occasion of the 300th anniversary of his death. The 16th century book collection was catalogued and published in 2005 by V. Magić (The Catalogue of 16th Century Books in the Metropolitan Library in Zagreb) It contains alphabetical lists of authors, titles, subject headings, names and places of publication and the preface in Croatian, German and English. For the purposes of this presentation, I started creating a list of 18th century books ; library's 18th century collection provides a good basis for research of the cultural history of Zagreb and its surrounding area. The records so far made include the information gathered from the first five catalogue boxes, out of the total number of 36 boxes, altogether 1489 books have been analyzed from the 18th century collection. For this presentation I focused my analysis on the information relating to language, content/subjects and the publication cities Language From the total of 1489 books, 684 (or 45.9%) were written in Latin. This number also includes a small number of Latin translations. The number of German books amounts to 481, (or 32.3 %), and comprises a large number of those originally written in German, but also some books translated into German from English, French, Danish, Dutch, Hungarian, Italian, Spanish which shows that the German language was in widespread use. The Italian language is represented with 156 books, (or 10.4%), the French language with 135 books, (or 9%), including both originally written, and translated from, for example, Arabian and Greek, which is the case with only a small number of books. 10 books were written in Croatian (in the kajkavian dialect) Topics The analysis of the content of the books was based on the catalogue cards for the total of 1451 titles. In certain cases the topic was not clear enough or there was insufficient information. As was expected, the collection shows a predominant number of theological books and religious topics, Books on saints, preaching and biblical topics ; altogether 590 titles, or (38.7 %) which is less than half the collection. 163 books or 11% represent historical topic, in addition to church related history. There are 146, or 10% legal books, 59 or 4% letters and speeches for various occasions, and 14 books or 0.8 % on politics. There is a rather large number, 108 or 7.1 % of literary books such as novels, short stories, prose poems, plays, works of Roman and Greek writers, poetry ; dictionaries and grammar books amount to 48, or 3.3% of the collection. Philosophy is represented with 37 titles, 2.5% Teaching, new ideas on education are represented by 85 or 5.7% books by German and French authors. A wide range of topics and interests of the period is also represented by books dealing with topics in natural sciences. The biggest number of them is books in medicine, 63 items, or 4.8% mostly written in German. Other branches of natural science are represented with 48 or 3.3 % books, among which the most important are works by Ruđer Bošković. A language analysis also points to a number of various places of publication. Dominant are the publishers from the cities with a long printing tradition such as Augsburg (57 items), Venice (the biggest number of items – 244) and Vienna (232), Leipzig (60), religious books from Rome (29). Old centers such as Florence (5), Nürnberg (6), are represented with a small number of items. New printing centers are represented - such as Paris (74), and cities from the German-speaking territory: Berlin, (23), Frankfurt-Leipzig, (18), Göttingen, (17), Halle (18), Hamburg, (13) and Cologne (20), and Bratislava, (26), Pest (Budapest) (11), Graz (17), Trnava (47). Especially valuable is the information on the publishers. We can find out names of 9 publishers in Augsburg, 23 in Leipzig, 17 in Rome, 32 in Paris, 47 in Venice, and the most about the publishers in Vienna, 53 of them. Most significant information for the history of printing in Croatia is related to printing houses in Zagreb. There are 9 of them, and with 48 published books they make a significant part of the collection. The analyzed data on the 18th century collection in the Metropolitan Library offers the possibility of a partial reconstruction of cultural circumstances in Zagreb of the period, and widespread of Enlightment ideas due to Bishop Vrhovac. These interests included new ideas in education of children and youth, one of dominant topics of the period. Contemporary pedagogical journals show the up-to-dateness and exchange of ideas. There was also a strong interest in natural sciences, medicine, but also the latest invention in physics. The guiding principle of the period, progress in general, is evident in the topics on the advancement of livestock breeding and agriculture, as well as practical advice on bee keeping and beer production. However, the most interesting insight into interests and up-to-date ideas, especially those of Bishop Vrhovac, are provided by the books dealing with law and politics. They show how much he followed contemporary affairs and circumstances, primarily numerous books that focused on analyses of crucial events such as the French revolution, books on the Jacobins, on the establishment and constitution of the United States of America, and especially interesting works on the great reformer, Emperor Joseph II. There are still a great number of questions which can be answered in the course of a comprehensive research project on this important collection. It is to be hoped, that, after more than one century of inappropriate conditions and insufficient staff, the books of the Metropolitan Library will be completely catalogued, classified and researched and thus become more accessible to researchers and the general public.
Projekt MZOS
ENG